Socioeconomic Inequalities in Child Oral Health: A Comparison of Discrete and Composite Area-Based Measures - Jason M. Armfield, BA (Blackwell Synergy, 2007)
This study aims to examine the relationship between child caries prevalence and six discrete area-based measures of socioeconomic status (SES).